2023
DOI: 10.1039/d2sc05105b
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalate–peptide hybrid materials: from structure–property relationships to applications

Abstract: Organo-functionalisation of polyoxometalates (POMs) represents an effective approach to obtain diverse arrays of functional structures and materials, where the introduction of organic moieties into the POM molecules can dramatically change...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…Furthermore, it should be noted that the presence of biomolecules in solution can impact the stability and behavior of POMs (50,51). In particular, POM-protein and POM-peptide interactions are complex and important areas of research that must be considered in many biological applications (52)(53)(54). These interactions can influence the efficacy and specificity of POMs in various biological contexts, making their study of great importance in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it should be noted that the presence of biomolecules in solution can impact the stability and behavior of POMs (50,51). In particular, POM-protein and POM-peptide interactions are complex and important areas of research that must be considered in many biological applications (52)(53)(54). These interactions can influence the efficacy and specificity of POMs in various biological contexts, making their study of great importance in the field.…”
Section: Discussionmentioning
confidence: 99%
“…This is especially highlighted in a recent review detailing the synthetic routes to obtain POM-peptide hybrid materials as well as their promising properties and applications. [92] The high interest in the synthesis of HPOMs based on the Anderson-Evans structure functionalized with biologically relevant molecules is likely due to the ease of its synthesis and post-functionalization. [93] However, it has been recently shown that Mn-centered Anderson-Evans HPOMs are not completely stable in aqueous media as they tend to be hydrolyzed over time, resulting in the release of the triol ligand and decomposition of the POM core into molybdate and Mn 3 + .…”
Section: Tailoring Pom-protein Interactions Through Organic Functiona...mentioning
confidence: 99%
“…Therefore, such reports highlight the vast potential of covalent functionalization to achieve novel POM‐based bio‐hybrids with tailored bio‐functionalities. This is especially highlighted in a recent review detailing the synthetic routes to obtain POM‐peptide hybrid materials as well as their promising properties and applications [92] …”
Section: Tailoring Pom‐protein Interactions Through Organic Functiona...mentioning
confidence: 99%
“…15−17 This nanotechnology-driven chemical engineering was made possible by utilizing DNA as the bioligation source and DNA origami as the ad-layer for the POV6 compounds with high relevance for medical biochemistry. 18−23 It is noteworthy that despite advances in the study of the reactivity of charged metal−oxo clusters to biomolecules 24,25 (amino acids, peptides, and proteins), there has been a lack of knowledge regarding their direct interaction with DNA 26−30 and the resulting properties until now.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The spatially well-regulated deposition, well-defined nanostructuring, and external electrical contacting of such solution-processed POMs as single molecules on conducting and semi-conducting surfaces are, however, some of the biggest challenges in POM-based molecular nanoscience, particularly due to the tendency of unfunctionalized POM anions to undergo vast speciation and agglomeration in solution and due to yet-ununderstood dynamics of POM countercations on the nanoscale . Using a post-functionalization synthetic route, we now succeeded to position single, DNA-augmented hexavanadate (POV6) anions with nanometer-level precision on a biomolecular DNA origami carrier structure that is immobilized on a biomedically relevant material, gold, which is given here by a model Au(111) substrate for scanning probe analyses. This nanotechnology-driven chemical engineering was made possible by utilizing DNA as the bioligation source and DNA origami as the ad-layer for the POV6 compounds with high relevance for medical biochemistry. It is noteworthy that despite advances in the study of the reactivity of charged metal–oxo clusters to biomolecules , (amino acids, peptides, and proteins), there has been a lack of knowledge regarding their direct interaction with DNA and the resulting properties until now.…”
Section: Introductionmentioning
confidence: 99%